Transient Anosmia and Dysgeusia in COVID-19 Disease: A Cross Sectional Study - Ali FA; Jassim G; Khalaf Z; Yusuf M; Ali S; Husain N; Ebrahim F (International Journal of General Medicine, 2023)
Fatema Ahmed Ali,1 Ghufran Jassim,2 Zahra Khalaf,3 Manaf Yusuf,4 Sara Ali,5 Nada Husain,6 Fatema Ebrahim6 1Department of Internal Medicine, South West Acute Hospital, Western Health and Social Care Trust, Enniskillen, Northern Ireland, UK; 2Family Medicine Department, Royal College of Surgeons in Ireland — Medical University of Bahrain (RCSI Bahrain), Busaiteen, Kingdom of Bahrain; 3Department of Postgraduate Studies, Royal College of Surgeons in Ireland, Dublin, Ireland; 4Children’s & Adolescent Services, Leeds General Infirmary, Leeds Teaching Hospitals NHS Trust, Leeds, UK; 5Ministry of Health Bahrain, COVID-19 National Team, Sanabis, Kingdom of Bahrain; 6Department of Internal Medicine, Private Health Sector, Manama, Kingdom of BahrainCorrespondence: Ghufran Jassim, Family Medicine Department, Royal College of Surgeons in Ireland — Medical University of Bahrain (RCSI Bahrain), Busaiteen, Kingdom of Bahrain, Email gjassim@rcsi-mub.comObjective: This study aims to explore the prevalence of anosmia and dysgeusia and their impact on COVID-19 patients.Methods: This is a cross-sectional study. Patients diagnosed with COVID-19 between 1st October 2020 and 30th June 2021 were randomly selected from a national COVID-19 registry. COVID-19 cases were diagnosed using molecular testing method which measured the viral E gene. The Anosmia Reporting Tool, and a brief version of the questionnaire on olfactory disorders were used to measure the outcomes via telephone interviews. Data were analysed using SPSS 27 statistics software.Results: A total of 405 COVID-19 adults were included in this study, 220 (54.3%) were males and 185 (45.8%) were females. The mean±SD age of participants was 38.2 ± 11.3 years. Alterations in the sense of smell and taste were reported by 206 (50.9%), and 195 (48.1%) of the patients, respectively. Sex and nationality of participants were significantly associated with anosmia and dysgeusia (p < 0.001) and (p-value=0.001) respectively. Among patients who experienced anosmia and dysgeusia, alterations in eating habits (64.2%), impact on mental wellbeing (38.9%), concerns that the alterations were permanent (35.4%), and physical implications and difficulty performing activities of daily living (34%) were reported.Conclusion: Anosmia and dysgeusia are prevalent symptoms of COVID-19 disease, especially among females. Although transient, anosmia and dysgeusia had considerable impact on patient’s life. Neuropsychological implications of COVID-19 in acute infection phase and prognosis of anosmia and dysgeusia in COVID-19 are areas for further exploration.Keywords: anosmia, taste, smell, COVID-19, dysgeusia, quality of life